Temporal and Locational Flexibility of Work, Working-Time Fit, and Job Satisfaction - Daniel Possenriede; Janneke Plantenga (Institute for the Study of Labor (IZA), 2014)
In this paper we analyse the effects of arrangements that provide temporal and locational flexibility of work (TLF), namely flexi-time, telehomework, and part-time work, on employees' satisfaction with the fit between working time and private life and their overall job satisfaction. TLF arrangements provide employees with more control over their working life and therefore are likely to improve on the match between paid work and private life. Based on Dutch household panel data, the results show that TLF arrangements, flexi-time in particular, are generally associated with sizeable increases in satisfaction with working-time fit and overall job satisfaction. Somewhat surprisingly, the effects hardly differ between male and female employees and between employees with and without children. Temporal and locational flexibility apparently appeals not only to employees with family responsibilities but more general to all employees.
Keywords: J22; J28; M52; M54; 330; flexi-time; job satisfaction; locational flexibility; part-time work; telehomework; temporal flexibility; working-time fit